Spatio-temporal evolution and convergence patterns of E-commerce development in China: Regional disparities and policy implications - Yuhuan Wu; Haisong Wang; Daqun Guo; Yan Li; Hang Zhang; Tianyuan Shan (PLoS ONE, 2025)
The rapid development of e-commerce has become a key driver of economic transformation and regional development in China. However, significant spatial and temporal disparities persist across regions. Understanding these disparities is essential for promoting balanced growth and maximizing the potential of e-commerce in fostering regional economic integration. However, existing studies often focus on isolated temporal trends or spatial patterns, lacking a comprehensive analysis that integrates spatial-temporal dynamics and examines the convergence trends of e-commerce development. This study aims to address these gaps by investigating the spatial-temporal distribution characteristics of e-commerce in China and assessing its convergence trends across different regions. This study utilizes panel data from 31 Chinese provinces spanning the period 2013-2023, employing spatial statistical methods, σ-convergence and β-convergence models, and regression analysis to identify the key factors influencing the observed disparities. The study finds that China’s e-commerce development is characterized by significant regional differences, the coexistence of polarization and low density, and different regional convergence trends in different regions, which provides an important theoretical basis for formulating differentiated development strategies, strengthening cross-regional infrastructure synergies, and digital technology innovation.